Characteristics of coastal saline soils inhabiting halophytes and salt tolerant plants - ARORA, SANJAY; MEHTA, RIDDHI (Journal of Soil and Water Conservation, 2018)
The present investigation has shown 8 plant species as dominant halophytes and salt tolerant that occurs in Bara tract salt affected region of Gujarat. Soil samples from the rhizosphere of different halophytes and salt tolerant plant species were collected for physico-chemical analysis. Almost all the soils were alkaline in reaction, because all the soils were of pH values above 8 with high EC values (0.55 to 82 dS/ m), indicating prevalence of moderate to high salinity conditions in the root zone region of the selected plant species. The organic carbon content was low in rhizospheric soil of Leucaena leucophala and high in Suadea nudiflora. The water holding capacity of soils from the rhizosphere of different halophytes and salt tolerant plant species was observed to be high. The ionic content in the soils collected from the rhizosphere of various halophytes and salt tolerant plant species was very high. From the fertility status of the various rhizospheric soil samples, it was found that the highest value of available nitrogen was found in the rhizospheric soil sample of Acacia nilotica and the lowest value was found in the rhizospheric soil sample of Suadea nudiflora. The highest value of available P content of soil was found in the rhizospheric sample of Prosopis cineraria.